Chilaiditi syndrome in a child with cerebral palsy presenting with recurrent abdominal pain - Esra Türe; Aynur Karaca; Fatma Dilşad Aksoy; Seda Sinem Yurdaor (SERNEV, 2021)
Introduction: The hepatodiafragmatic interposition of colon is called Chilaiditi sign. For symptomatic patients, the term "Chilaiditi syndrome" is used, this term was first reported in 1911 by Demetrius Chilaiditi, a Viennese radiologist, in three asymptomatic patients. Patients are commonly asymptomatic, and some patients may apply with gastrointestinal or respiratory symptoms such as abdominal pain or chest pain. In the study of Lekkas et al, the incidence of Chilaiditi syndrome in mental retarded patients was reported to be 63 times higher than normal population.Case Presentation: High liver dome and elevated right diaphragm, hepatic flexura replaced between liver and anterior wall of abdomen were observed in chest radiography and abdominal computer tomography of our 6,5 year old male patient with cerebral palsy who has mental retardation and recurrent abdominal pain in medical history.Conclusions: In conclusion, Chilaiditi syndrome should be considered in mental retarded children with recurrent abdominal pain.Keywords: Child, chilaiditi syndrome, recurrent abdominal pain, mental retardation, cerebral palsy